Insights into Regulation of the miR-17-92 Cluster of miRNAs in Cancer - Fuziwara, Cesar Seigi; Kimura, Edna Teruko (Frontiers in Medicine, 2015)
Overexpression of the miR-17-92 cluster is a key oncogenic event in various cancer types. The oncogenic effect of the miR-17-92 cluster is enhanced by cooperation between its members in targeting tumor-suppressive proteins and pathways such as PTEN and TGFβ signaling. However, in the case of miR-19a and miR-19b, these have been shown to have a preponderant role in the cluster’s oncogenicity. Important studies have revealed the influence of the Myc proto-oncogene family in the transcriptional regulation of miR-17-92. Recent findings show that other oncogenic signaling pathways, such as those of Notch and Sonic Hedgehog, activate miR-17-92 in cancer. Notwithstanding, another layer of complexity has been added by the influence of the relevant primary miR-17-92 tertiary structure during processing to mature miRNA. In this review, we attempt to integrate current transcriptional and post-transcriptional knowledge to enhance our global understanding of the coordinated up-regulation of miR-17-92 in cancer.